Sustainable management of sweet potatoes: A review on practices, strategies, and opportunities in nutrition-sensitive agriculture, energy security, and quality of life - Tedesco, Danilo [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; Maeda, Murilo; Silva, Rouverson Pereira da [UNESP] (Elsevier, 2023)
CONTEXT: Sweet potatoes are sources of staple food for human nutrition and welfare. Hence, they can assist in developing food security in vulnerable communities. Equally significant, they offer industries suitable feedstocks to fabricate biofuels. OBJECTIVE: We reviewed the literature to establish practices, strategies, and opportunities in producing them for nutrition-sensitive agriculture, energy security, and quality of life. METHODS: We defined Web of Science™ and Science Direct® as databases to select scholarly items to develop our driving bibliographic collection. We combined keywords and Boolean operators into search-engining strings, such as ALL = [“sweet potato” AND (“fertilization” OR “irrigation” OR “pest control” OR “breeding”)], to strike them. We limited our search to peer-reviewed papers to address a methodologically sound approach. We assessed them for consistency and eligibility by reviewing titles, highlights, abstracts, keywords, methods, conclusions, and declarations (i.e., financial support and acknowledgment). We conducted our review independently. Nevertheless, we discussed them collectively to handle divergent opinions and intellectual conflicts. RESULTS AND CONCLUSIONS: We obtained sufficient and significant bibliometric data to elaborate on trending topics, such as nutrition-sensitive agriculture, food-fuel divide, and remote sensing for site-specific monitoring and intervention. Genotypes containing higher quantities of carotenoids and anthocyanins can contribute to human nutrition and welfare. They assist individuals in producing vitamin A and antioxidants, preventing xerophthalmia and malignant tumors. Some others are multi-objective, offering resources for consumption and processing into bioethanol. Hence, they can decrease conflicts in selecting edible tubers for bioenergy production. Genetic breeding can allow their cultivation in challenging environments, such as drylands, as it improves their response to fertilization and irrigation. Exploiting locally available fertilizers, controlling economically relevant pests biologically and culturally, and selecting healthy propagative material (i.e., vines) can further contribute to their cost-effectiveness, environmental footprint, and longevity. Equally significant, producers can benefit from high-resolution remote sensing data to monitor, map, and intervene in their fields early and precisely, avoiding risky seasons. SIGNIFICANCE: Our review stresses the sustainable production of sweet potatoes as specialty crops for sustainable development. Hence, its ramifications offer stakeholders, such as producers, researchers, and policymakers, catalytic, actionable knowledge to address pressing economic, environmental, and social issues. They can consider them in elaborating on physically and financially accessible diets and equitable, responsive rural arrangements for people in vulnerable regions. It can assist in mitigating hunger and malnutrition while creating opportunities and possibilities for farmers and consumers to produce and afford health-promoting, nutrient-dense tuberous roots.
Keywords: Farming systems; Food security; Highly nutritive edible roots; Ipomoea batatas; Remote sensing; Transformative agriculture